PARTISIPASI MASYARAKAT DALAM KEBERLANJUTAN PENGELOLAAN BANK SAMPAH DI DESA SEMAMUNG - Burhanuddin; Harjito; Trishuta Pathiassana, Mega; Trishuta Pathiussina, Rimba (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
The role of the Waste Bank became important with the issuance of Government Regulation (PP) No. 8 of 2012 concerning Management of Household Waste and Household-Like Waste. The Semamung village waste bank is a waste bank that is still active and productive compared to other waste banks in Sumbawa. Therefore, this study aims to determine community participation and the factors that influence the level of community participation in Semamung Village, Sumbawa Regency in waste bank management. The data collection technique used purposive sampling technique with qualitative methods. Based on the results of research that has been carried out in Semamung Village, from about 478 Heads of Families (KK), only about 18 households are still active in participating in the Friends of Semamung Village Waste Bank and the factors that influence community participation in the Semamung Village Friends Waste Bank program are the number of family members, gender, age difference, and low socialization carried out by the management of the Semamung Village Friends Waste Bank. This study concludes that the participation of the Semamung Village community in the Friends Waste Bank program is still relatively very low.